From ‘Criminal Acts’ to ‘Crimes’ and Accountability: A Philosophical Study of the Aspects of Fault and Punishment in Law No. 1 of 2023 - Nissa, Khaoeirun (Dinasti Research, 2025)
This study aims to discuss the change in the status of criminal acts to criminal offenses and a study of the accountability of aspects of errors in criminalization as stated in Law No. 1 of 2023. This research is a qualitative research. Library research is used in this normative legal research methodology. The particulars of this study include the use of descriptive analysis as the research methodology. Primary and secondary legal materials comprise the secondary data sources and kinds used in this study. The approach to data analysis is normative. According to the findings of the study, Law Number 1 of 2023 pertaining to the Criminal Code embraces neo-classical principles and strikes a balance between objective and subjective considerations. The types of penalties regulated, the acceptance of living law as a basis for sentencing, the consideration of humanitarian aspects, and the adoption of a new concept that emphasizes prevention, rehabilitation, and conflict resolution without degrading human dignity all of which are significant changes to criminal law.